Can Computer-Based Instruction Improve Molecular Biology Comprehension Among General Education Students? - Christine A. Genovese (Networks: An Online Journal for Teacher Research, 2003)
The study compared the efficacy of teaching key concepts of molecular biology using an online study environment with a more traditional, lecture-based approach. Two introductory biology classes were randomly divided and exposed to one of two instructional delivery systems. The traditional group attended class and heard lectures covering DNA structure and replication, RNA transcription and protein synthesis, and had live interaction with the instructor. The remaining students used computer-based instruction exclusively to cover the identical course content. These, so called, online learners had access to web pages with detailed lecture notes that were supplemented with graphics, animations and hyperlinks. They interacted with the instructor, and completed chapter quizzes, using electronic mail. Results of a multiple-choice final examination revealed significantly poorer performance by the online group (Mdns = 48% vs 60%, p< .025). Student feedback indicated that the online learning experience was perceived to be more solitary, require more time and personal responsibility. Implications for computer-based instruction were discussed.